2006
DOI: 10.1111/j.1365-2850.2006.00981.x
|View full text |Cite
|
Sign up to set email alerts
|

A survey of mental health nurses’ experiences of stalking

Abstract: Although an increasing amount of literature has appeared in recent years on the subject of stalking, little is known about mental health nurses' (MHNs) experiences of this phenomenon. The aims of the study were to investigate: (1) the incidence of stalking among a sample of MHNs in the UK; (2) who the perpetrators were; (3) the impact of stalking on MHNs; and (4) how MHNs manage their experiences. Employing a survey design, the British version of the Rutgers-Penn clinicians and stalking questionnaire was distr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
46
0
2

Year Published

2008
2008
2025
2025

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(54 citation statements)
references
References 18 publications
(48 reference statements)
6
46
0
2
Order By: Relevance
“…In absolute terms however, more female psychiatrists reported being victims of stalking (51%). This is consistent with a UK study of psychiatrists 11 and nurses 12 that found that more females (59% and 78.6% respectively) had been victims of stalking behaviour.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…In absolute terms however, more female psychiatrists reported being victims of stalking (51%). This is consistent with a UK study of psychiatrists 11 and nurses 12 that found that more females (59% and 78.6% respectively) had been victims of stalking behaviour.…”
Section: Discussionsupporting
confidence: 79%
“…However, in another UK study that looked at stalking of nurses, 12 82.1% of the stalkers were males.…”
Section: Discussionmentioning
confidence: 99%
“…Fifty percent of a convenience sample of 112 mental health nurses reported at least one stalking experience in their careers. However, the design of this study does not allow for generalization of this rate to all mental health nurses (Ashmore et al 2006). As noted earlier, a survey of 171 social workers found that 16.3% reported being stalked at some point in their careers (MacDonald and Sirotich 2005).…”
Section: The Incidence Of Stalkingmentioning
confidence: 98%
“…A survey by Smoksy (2003) reported that 37% of nurses had been stalked, a third by former mental health clients. In a larger UK sample, 50% of mental health nurses reported at least one stalking experience, again about one third of which were carried out by service users (Ashmore et al, 2006).…”
Section: Introductionmentioning
confidence: 99%